More efficient proof-search for sequents of temporal logic - Alonderis, Romas (Lietuvos matematikos rinkinys, 2022)
The present paper deals with efficiency improvement of backward proof-search of sequents of propositional linear temporal logic, using a loop-type sequent calculus. The improvement is achieved by syntactic transformation of sequents into equivalent to them simpler ones. It is proved that some formulas can be removed from sequents with no impact on their derivability.